Anaslisis Kesantunan Berbahasa Menurut Leech pada Tuturan Berbahasa Arab Guru Pondok Pesantren Ibnul Qoyyim Putra Yogyakarta Tahun Ajaran 2016/2017 (Kajian Prgmatik) - Wahidah, Yeni lailatul; Wijaya, Hendriana (Universitas Islam Negeri Raden Intan Lampung, 2017)
Abstract: This research is aimed to find out the structure of Arabic speech that is used by the teacher and the politeness aspects of language in Arabic speech which is used by Ibnul Qoyyim Boarding School For Boys when teaching santri in classroom. This research is a qualitative research by collecting data by interacting with people in place of research. The method that researchers use in this study is divided into three namely the method of data provision, data analysis, and methods of data analysis results. After analyzing the direct speech by the subject teacher of Tamrin Lugah in Ibnul Qoyyim Boarding School For Boys with the theory of politeness of Geoffey Leech, it resulted in the tact maxim of 17 speeches, the generosity maxim of 4 speeches, the approbation maxim of 14 speeches, the agreement maxim of 25 speeches, and the sympathy maxim of 4 speeches. Whereas in practice the teacher also violated the language-assisted language with the tact maxim of 13 speeches, the approbation maxim of 2 speeches, and the aggrement maxim of 7 speeches, and researchers did not find the modesty maxim. Keywords: institution, language politeness, teacher's speech